La demande de bois-énergie à Ouagadougou : esquisse d’évaluation de l’impact physique et des échecs des politiques de prix - Boukary Ouedraogo (Développement Durable et Territoires)
This paper aims at evaluating not only the wood-energy demand of Ouagadougou, the physic impact of this city wood energy consumption on the forest of its provisioning area, together with the causes of wood-energy price policy failures. The evaluation’s methods of wood energy consumption are reviewed in comparison with the resource supply conditions and the availability on data of wood resource demand. The data on the forest inventories of the wood-energy provisioning surface of Ouagadougou, as well as investigations into the households and the craftsmen allows estimating the consumption of Ouagadougou in wood-energy and its impact on the forest resources’ depletion. some complementary analysis have been done on the main causes of wood energy price policy failures.